On the Source of the Anomalous ULF Waves Detected at Both Ground and Space‐Borne Data on 23 June 2020. Issue 2 (22nd February 2022) - Piersanti, M.; Di Matteo, S.; Zhima, Z.; Yang, Y.; Zhang, Z.; Marcucci, M. F.; Parmentier, A.; D'Angelo, G.; Recchiuti, D.; Diego, P.; Ubertini, P.
Abstract: We have analyzed a highly monochromatic ( f  = 1.67 mHz) and large‐amplitude Ultra Low Frequency (ULF) wave event observed at satellites and ground observatories on 23 June 2020 during super solar quiet geomagnetic conditions. The train wave was detected between 6:22 and 7:55 UT across a wide longitudinal range of ground stations from low to high latitudes. Using Deep Space Climate Observatory and THEMIS‐B spacecraft, which were in the interplanetary medium, we have identified the possible driver of such global ULF wave activity in the impact of a small pressure pulse accompanied by a discontinuity in the magnetic field. The prolonged duration (90 min) of the ULF waves as well as their latitude‐independent frequency and the small azimuthal wave number ( m ∼ 0−2) can be explained in terms of a global magnetospheric waveguide mode. The amplitude and cross‐phase analysis of the wave activity at ground, together with the polarization pattern, suggest the waveguide mode coupling with field line resonance. Nevertheless, during the same time interval, indirect evidence exists of a rapid reconfiguration of the magnetotail in the form of Pi2 waves in the night‐side region. The analysis of energetic particle flux at ionospheric height (500 km) shows a direct connection between the ULF wave activity and particle precipitation. Plain Language Summary: Ultra Low Frequency (ULF) waves illustrates the highly dynamical nature of the Earth's magnetosphere since they are directly connected with energy and mass transport. The event we analyzed occurred during a very low geomagnetic activity showing 10 min period (Pc5) waves between 6:22 and 7:55 UT across a wide longitudinal range of ground stations from low to high latitudes that lead to particle precipitation. The prolonged duration (90 min) of the ULF waves as well as their latitude‐independent frequency and the small azimuthal wave number can be explained in terms of a global magnetospheric waveguide mode. The latitude and local time polarization pattern of the Pc5 wave event, suggests the waveguide mode coupling with magnetospheric field line resonances. The satellite observations in the interplanetary medium suggest that small solar wind disturbances were able to trigger the dynamic of the system directly, with Pc5 waves in response to the impact of a small jump in dynamic pressure, and indirectly, together with a rotation of the interplanetary magnetic field, triggering magnetotail processes resulting in an additional higher frequency wave activity (Pi2). Such kind of studies need scrupulous attention when trying to identify the possible source of ULF wave activity. Key Points: Global magnetospheric anomalous Ultra Low Frequency waves activity during super solar quiet conditions Coupling between the waveguide mode and magnetospheric field line resonance Signatures of particle precipitation at Low Earth Orbit orbit during Pc5 and Pi2 wave activity